The stories we tell : how to use story and storytelling to improve teaching and school leadership - Bromley, Matt (Abingdon, Oxon ; New York, NY : Routledge, 2025)
"Stories give meaning to our lives and make us who we are. They shape our self-awareness, thus helping make sense of personal experiences, no matter how complex or difficult. Stories can also have a profound impact on our behaviours, values, and attitudes. This exciting new book examines the powerful role stories can play in schools both as a curriculum/teaching tool and as a framework for school improvement. The Stories We Tell looks holistically at the uses of story in schools and sets out the ways it can be used to support teaching, including by: Organising the curriculum and helping to structure lessons Aiding students' memorisation Promoting inclusion Preparing students for future success. In addition, it offers four ways of using story and storytelling in the school improvement process to: Consult, communicate and collaborate with stakeholders to the school improvement journey Articulate a vision for the future and foster a set of shared values Build trust and adopt ethical leadership behaviours to create a no-blame culture that encourages risk-taking Resolve conflict and manage people, and lead change and manage PR Providing a fresh and stimulating approach to teaching and learning, curriculum-development, and school improvement, this will be valuable reading for teachers and school leaders across the primary and secondary phases"--
Part One: Learning through storytelling -- Chapter 1: The power and the story -- Chapter 2: The stories we tell ourselves -- Chapter 3: The stories we tell our children -- Chapter 4: The stories of literacy -- Chapter 5: The stories beyond comprehension -- Part Two: Teaching through storytelling -- Chapter 6: Using story to organise the curriculum and structure lessons -- Chapter 7: Using story to aide memorisation -- Chapter 8: Using story to engage learners' curiosity and wonder -- Chapter 9: Using story to relate curriculum content to the real world -- Chapter 10: Using story to help foster inclusion -- Chapter 11: Using story to prepare learners for future success -- Part Three: Leading through storytelling -- Chapter 12: Using story to consult, communicate and collaborate -- Chapter 13: Using story to articulate a vision and foster shared values -- Chapter 14: Using story to build trust and create a no-blame culture -- Chapter 15: Using story to resolve conflict -- Chapter 16: Using story to lead change.
Keywords: Storytelling in education; Communication in education; School improvement programs; EDUCATION / Secondary; EDUCATION / Elementary; EDUCATION / Leadership